Modthryth and the Problem of Peace-Weavers: Women and Political Power in Early Medieval England. Issue 6 (18th August 2021) - Sebo, Erin; Schilling, Cassandra
ABSTRACT: Modthryth has been largely understood as an early example of a character archetype common in Western culture, the wicked queen. She is read as a parable warning of the dangers of allowing women to exercise power. Such a reading has anachronistically aligned the cultural attitudes of the audience of Beowulf with those found in the works of later chroniclers, such as Roger of Wendover, Matthew Paris, John of Worcester, and William of Malmesbury, whose accounts of historical medieval English queens such as Cynethryth and Ælfthryth, are permeated with this anxiety. However, unlike these later chronicles, Beowulf is positive in its depiction of queens exercising power. In this paper, we argue that the treatment of Modthryth is, in fact, very similar to that of kings in the poem and that she is judged by the same measure and discussed in the same vocabulary as other powerful figures. We argue that the digression should be read in terms of an entirely different cultural issue and one which has been largely ignored: the emotional difficulties of being a peace-weaver.